2006
DOI: 10.2135/cropsci2005.0272
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Yield Stability of Intersubspecific Alfalfa Hybrids

Abstract: Long-term persistence and sustained biomass yields of alfalfa (Medicago sativa L.) stands are important to producers. Yield performance and persistence of intrasubspecific crosses between alfalfa subspecies sativa and falcata after the first post-establishment year are unknown. The objectives of this study were to measure biomass yields, persistence, and biomass yield stability in inter-and intrasubspecific alfalfa crosses derived by mating nine elite sativa clones and five falcata clones in a half-diallel. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The hybrids produced higher biomass yield through the spring growth of the first post-establishment year, compared to red clover but lower in the subsequent year. Similar results have been obtained for intersubspecific sativa by falcata alfalfa (Medicago sativa L.) hybrids (Riday & Brummer 2006).…”
Section: Discussionsupporting
confidence: 86%
“…The hybrids produced higher biomass yield through the spring growth of the first post-establishment year, compared to red clover but lower in the subsequent year. Similar results have been obtained for intersubspecific sativa by falcata alfalfa (Medicago sativa L.) hybrids (Riday & Brummer 2006).…”
Section: Discussionsupporting
confidence: 86%
“…This research was extended to hay production systems, revealing that the slower regrowth potential of falcata types was not adapted to intensive production and therefore not currently a useful source for heterosis (Riday and Brummer, 2004). Evaluation of persistence in these crosses have also shown that falcata persistence needs to be improved (Riday and Brummer, 2006). However, research in Australia has highlighted the potential for falcata germplasm to improve yield, including detection of substantial specific combining ability effects in Queensland test environments .…”
Section: A Cultivar Typesmentioning
confidence: 99%
“…Genotypes respond differently to environmental factors such as soil fertility or the presence of disease pathogens (Kang, 2004). These contribute to genotype ´ environment interaction (G´E), which has been reported in field and vegetable crops (Bednarz et al, 2000;Mekbib, 2003;Riday and Brummer, 2006;Fan et al, 2007;Mulema et al, 2008;Miranda et al, 2009;De Vita et al, 2010;Panthee et al, 2012;Rak et al, 2013).…”
mentioning
confidence: 99%